Bringing Happiness into Family Circles in McDonald’s Advertisements - Stella Angela; Samuel Gunawan (Kata Kita: Journal of Language, Literature, and Teaching, 2023)
This study was conducted to analyze verbal and visual expressions used in McDonald’s video advertisements. In the video advertisement, the writer focuses on how family circles create the idea of happiness through verbal and visual expressions. The writer observed using the multimodality theory by Paltridge (2012) and Gee (2004). The writer used the qualitative content approach in this study. The finding of this study shows that “Togetherness” is the main key to creating the idea of happiness in family circles from  McDonald’s advertisements. More studies involving other themes and semiotic elements are recommended for further study. The result of this study will show how verbal expressions will reveal the idea of happines by stating all the keywords. At the same time, visual expressions will reveal how the idea of happiness can be seen with the help of some elements like colour scheme, clothes, place, expressions, and gestures.